PKM FOR DEVELOPMENT OF SPORTS FACILITIES ON HANDAYANI STREET I, RW XIV - Dian Wahyoni; Danyl Mallisza; Adrian Fadhli; Hardi Wijaya; Nazili, Nazili; Robby Hotter (Ikatan Dosen Menulis, 2024)
This Community Service Activity (PKM) was carried out by lecturers from the Civil Engineering Study Program, Faculty of Engineering and Planning, Ekasakti University, with the aim of building sports facilities on Handayani Street I, RW XIV. The project is designed to provide adequate sports facilities to support physical health and improve the social cohesion of the local community. Implementation methods include planning, coordination with related parties, technical implementation, as well as evaluation and monitoring. The results show that the sports facilities built meet quality standards and have been well used by the community, providing significant physical and social benefits. Active community involvement increases the sense of ownership and responsibility for the facility, supporting its sustainability. The success of this project emphasizes the importance of synergy between universities, government and society, and shows the need to consider social and cultural aspects in service projects. This activity strengthens the role of universities in sustainable community development.